COMMUNITY STRUCTURE OF MACROZOOBENTHOS IN MANGROVE FOREST AREA OF RANGSANG ISLAND MERANTI ISLANDS REGENCY - Rusadi, M Dio Eigmar; Siregar, Sofyan Husein; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTMacrozoobenthos are benthos animals that live in the bottom as well as the surface substrate. One of themacrozoobenthospreferred habitat is mangrovearea. Macrozoobenthos community structure is influenced by environmental changes. This research was conducted on January 2018 in Rangsang Island Meranti Islands Regency that aims to find out the community structure of macrozoobenthos included species, abundance, diversity, uniformity, dominance, sediment organic matters, and environmental parameters in mangrove area of Rangsang Island Meranti Islands Regency. The method sampling used line transect in 3 stations. Macrozoobenthos that found in this research are 12 species with 1.88 – 8.55 ind m-2. The value of diversity index (H’) is 0.18 - 2.80, dominance index (C) with ranged 0.27 - 2.21, and uniformity index (E) with ranged 0.47 - 2.80. The content of sediment organic mattersranged 6.21 - 15.69% for each station. Keywords:Macrozoobenthos, Community Structure, Sediment OrganicMatters